Long-term stability of an adult Class III open-bite malocclusion treated with multiloop edgewise archwire - Chien-Chun Kuo; Yi-Jane Chen; Eddie Hsiang-Hua Lai; Chung-Chen Jane Yao; Jenny Zwei-Chieng Chang (Elsevier, 2009)
This case report describes the treatment of a 17-year-old girl with an anterior open- bite and Class III malocclusion, who had a history of thumb-sucking habit in childhood. The multiloop edgewise archwire technique was used on the mandibular arch to facilitate uprighting of the mandibular posterior teeth, change the cant of occlusal plane, close the anterior open-bite, and correct the Class III malocclusion. At the end of treatment, Class I occlusion and correction of the anterior open-bite had been achieved. An examination 8 years 8 months after treatment revealed long-term stability of the treatment results.